PROSODIC ORGANISATION OF STATIC URBAN LANDSCAPE DESCRIPTIONS IN ENGLISH PROSE - Inna Humeniuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
In the article on the basis of a systemic analysis of English landscape descriptions' functional, semantic and structural characteristics the author gives the most common definition of a landscape description, outlines the eight-level classification of their linguistic features, in which the main level of descriptions' identification is their belonging to the locality type. In the paper, the author performs a detailed analysis and modelling of language units' interaction in the landscape descriptions of oral actualisation. The model allows distinguishing the direction of prosodic, lexical and grammatical means' interaction in the organisation of the aforementioned descriptions having different degrees of their narrative dynamics and the level of emotional-and-pragmatic potential. The suggested model and the landscape descriptions' classification serve as methodological grounds for the experimental phonetic study of static urban landscape descriptions' prosodic organisation. The article also outlines the steps of the auditory analysis methodology necessary for researching the prosodic parameters of the descriptions under study. Among other parameters, the author applies the Kalyta-Taranenko K-criterion for the evaluation of a text fragment's level of emotional-and-pragmatic potential. The results of the auditory analysis enable the author to come up with the invariant prosodic pattern of English static urban landscape descriptions' intonation organisation. This invariant pattern makes it possible to classify them perfectly well during their oral realisation. The paper also outlines the prospective scientific studies of other kinds of descriptions in different linguistic spheres in general and in phonetics in particular.